Identification of the Causal Agent of Cocoa Pod Rot Disease from Various Locations - Indri Komalasari; Suryanti Suryanti; Bambang Hadisutrisno (Jurnal Perlindungan Tanaman Indonesia, 2018)
Cacao (Theboroma cacao L.) is an important estate commodity in Indonesia with high economic value. The interference of cocoa pod rot disease which was affected by Phytophthora palmivora Butl. resulted in the reduction of the quantity and quality of cocoa beans, with losses up to 44%. This research was aimed to figure out the variation in morphology of P. palmivora isolates from cacao. The research was carried out by collecting samples of cocoa pod with rot symptoms in several cacao growing areas in Java, then the pathogen was isolated and cultured on Potato Dextrose Agar (PDA) medium. The observation was performed on morphological characteristics of isolates macroscopically (colony shape) and microscopically (size of sporangium and chlamydospores). All tested isolates showed various colony shape such as stellate, cottony and irregular as well as sporangium varying from obpyriform, globose, ellipsoid, ovoid and distorted with various size between 30.8×21.9–65.5×46.5 µm in range.IntisariKakao (Theboroma cacao L.) merupakan komoditas perkebunan unggulan di Indonesia dengan nilai ekonomi tinggi. Gangguan penyakit busuk buah kakao yang disebabkan oleh Phytophthora palmivora Butl. mengakibatkan penurunan kuantitas dan kualitas biji kakao, dengan kerugian mencapai 44%. Penelitian ini bertujuan untuk mengetahui variasi morfologi isolat P. palmivora asal kakao. Penelitian dilakukan dengan mengambil sampel buah kakao bergejala busuk buah di beberapa area perkebunan kakao di Jawa, kemudian patogen diisolasi dan dikulturkan pada media Potato Dextrose Agar (PDA). Pengamatan dilakukan terhadap karakteristik morfologi isolat secara makroskopis (bentuk koloni) dan mikroskopis (ukuran sporangium dan klamidospora). Semua isolat yang diuji menunjukkan bentuk koloni seperti stellate, cottony, dan irregular serta sporangium yang bervariasi dari obpyriform, globose, ellipsoid, ovoid, dan distorted dengan ukuran bervariasi antara 30,8×21,9−65,5×46,5 µm.